The Effectiveness of Topical Tea Tree Oil (Terpinen-4-Ol) in Human Demodicosis: A Literature Review - Ayu Mayangsari; Ratih Pramuningtyas; Aulia Nissa Rizky Hariyono; Zhela Fatin Fatiha; Tia Mella Citra (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Demodecosis is a skin disorder caused by parasites with the demodicosis type. The primary cause of this condition in humans is two kinds of Demodex mites, D.folliculorum and D.brevis. Demodicosis are usually treated with TTO, but the effectiveness is not well documented. To evaluate the effects of topical Tea Tree Oil on demodicosis infestation in people. We use the following string in Google Scholar; PubMed; Science Directs with keywords (“Demodicosis”iORi“demodex”iOR"D.folliculorum"iORii"D.Brevis) ANDi (TTOiORiT4OiOR "tea tree oil"). The articles compatible with the restriction criteria then screened using the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) method.  The quality of the articles is tested using GRADE method. A total of 4 of 1949 articles recorded according to the inclusion criteria, all three articles were randomized clinical trials. 351 patients were treated with topical Tea Tree Oil (TTO) scrub with eyelash shampoo, the most common ocular symtomps is ocular dryness. The treatment is provided on a scale 18 to 35 years of age, topical TTO scrub with consentrated persentation 5-50% with eyelash shampoo was at twice-daily treament for 4 weeks. No serious side effect. Topical administration of Tea Tree Oil has shown a reduction in human demodicosis.